Analisis Sistem Pengendalian Internal dalam Pembiayaan Bai’ Taqsith Pada Koperasi Konsumen Syariah Arrahmah - Alya; Andriani (Indonesian Journal of Applied Accounting and Finance, 2023)
This study aimed to determine the application of internal control in bai’ taqsith financing at Arrahmah Sharia Consumer Cooperative using COSO standards. This research was conducted using qualitative approach. Primary data was gathered by conducting interview, while secondary data was obtained by documenting some written information. The results showed that the internal control system implemented by the Arrahmah Sharia Consumer Cooperative was quite good and in accordance with the components of internal control according to COSO. The internal control environment is created through integrity and ethical values for all employees and management. There are organizational structure, policies related to human resources and financing risk mitigation. Control activities take place quite well. Information, communication, and monitoring have also been implemented by this cooperative. However, there are still some weaknesses, namely the existence of duplicate functions in the marketing and financing analysis sections, the absence of an integrated financing information system, and the potential for fraud